Molluscan Shell Matrix Characterization by Preparative SDS-PAGE - Frederic Marin (The Scientific World Journal)
The glycoproteinaceous constituents of molluscan shell matrices usually resist chromatographical fractionation. We describe a protocol that overcomes this difficulty and permits collection of a large amount of shell proteins for further in vitro characterization. After dissolution of the mineral phase, the glycoproteins are fractionated blind on a preparative electrophoresis. They are subsequently detected with a polyclonal antibody raised against the whole matrix.